Caracterização, classificação e potencialização de uso dos solos do IFRR/ Campus Novo Paraíso - Pereira, Raimundo de Almeida (2014)
This work was conducted whit the objective of characterizing and classifying the soils of de federal Institute of Education, Science and Technology of Roraima – IFRR / New Paradise Campus, seeking recommendations of sustainable use end management. The soils were characterized as to their chemical, physical, morphological and mineralogical properties. For characterization of the soils, “pecks” were opened along random, precisely-measured distances, where borings and openings of 10 trenches were carried out for the description and collection of soil samples from March 2012 to June 2013. The chemical analyses carried out for Calcium (Ca), Magnesium (Mg) and Aluminum (Al) were extracted by KCl. For the Potassium (K), Sodium (Na) and phosphor (P), the Mehlich – 1 was utilized and its determination through a flame photometer, and the P by spectrophotometer of atomic absorption. The potential acidity was determined in a solution of calcium acetate. For the pH of H2O and KCl, the principle of electrochemical measurement of the principle of electrochemical measurement of the concentration was utilized. The total organic carbon was determined by the method of Walkley-Blak. The following classed of soils were classified up to the 4th categorical level of the Brazilian System of Soil Classification: Entisols Quartzipsamments, Ultisol Hapludult, Ultisol Hapludox, Ultisol Hapludults, Entisols Fluvaquets Hapludults, Entisols Fluvaquet, Oxisol - Kandiudox. Chemically, the soils were characterized as strongly acidic, dystrophic and with low natural fertility, possessing clay of low activity, with low levels of Al3+. The mineralogical analyses indicated soils with predominance of kaolinite in the clay fraction. The Neosol and Gleisols presented a textural variation light sandy, being more suitable for preservation of fauna and flora. The Plinthosols and the Latosol showed a textural variation, light sandy to light clay and light sandy loam, being able to be utilized for agricultural cultivation, with the utilization of techniques of management and conservation of the soil.